Comparison of the Exam Scores Obtained in Face-to-Face Education and Online Education by the Students of the Faculty of Dentistry - Mustafa Aydınbelge; Cansu Demiroğlu; Burcu Duman (Ankara University, 2021)
Purpose:The Covid-19 pandemic has affected our daily lives by affecting the whole world and caused our habits to change.One ofthe effects of the epidemic has been on education.With the spread of the epidemic, online education has become the only way to maintain the normal teaching order.In this case, it directly affects the quality of education received.The aim of this study is to examine whether there is a difference between the exam scores made face to face and online. Methods:Students who were 3rd grade in 2018-2019 and 4th grade in 2019-2020 academic year were included in the study.Thescores that these students got in the Pedodontics Theoretical Exam within two years were evaluated. Exam scores according to time were analyzed with Friedman Test and Wilcoxon Test. Results:In the 2019-2020 academic year, the median values of the scores obtained from the exams that took the first examface-to-face and the second and third exams online varied (p lt;0.001).The median values of the scores obtained in the online exams(median values of 90 and 95, respectively) (the mean values are 89.6±8.7, 93.8±9, respectively), the median values of the scores obtained from the theoretical exam (median 70, mean 67.2±18.1) was obtained higher.On the other hand ,it was observed that there was a significant increase between the scores obtained by the same students from the exams held face-to-face in the previous year(median 74, mean 74.1±7.1) and the scores they took from the online exams they obtained the next year (median 89, mean87.7±9.1)(p lt;0.001). Conclusion:The results of the exams made with the online system are higher than the exam scores performed face to face.Thismay be due to the insufficient control mechanisms of the online exam system.For this reason, online exam security measuresshould be increased.